2014
DOI: 10.1097/tp.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Effect of Late Acute Rejection on Renal Transplant Outcomes

Abstract: The prevalence and recurrence of LAR are considerable and associated with increased incidence of graft loss. Patients who need dialysis during LAR should be carefully evaluated owing to the high prevalence of graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…It is worth noting that 11 of these 17 ACRs occurred beyond 1 year after transplantation. Our findings that late ACR is responsible for graft failure are in broad agreement with the report of Rodrigues et al that late acute rejection is associated with graft failure …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is worth noting that 11 of these 17 ACRs occurred beyond 1 year after transplantation. Our findings that late ACR is responsible for graft failure are in broad agreement with the report of Rodrigues et al that late acute rejection is associated with graft failure …”
Section: Discussionsupporting
confidence: 93%
“…Our findings that late ACR is responsible for graft failure are in broad agreement with the report of Rodrigues et al that late acute rejection is associated with graft failure. 23 We reported that concurrent ACR and AMR rejection carries a poor prognosis. 24 In this study, only 3 of 27 graft failures due to AR were due to AMR biopsy diagnosis and 7 failures were due to mixed ACR and AMR.…”
Section: Discussionmentioning
confidence: 95%
“…Second, our cohorts show 51% of AR and 99% of “IFTA with AR” samples were diagnosed >1 year posttransplant. This finding confirms Scientific Registry for Transplant Recipients and DeKAF data and growing evidence that AR episodes often occur late posttransplant in both adult and pediatric populations .…”
Section: Discussionsupporting
confidence: 89%
“…PCRR typically occurs one or more years after transplantation. Although PCRR has been generally considered to be a subtype of T cell–mediated rejection (TCMR), cases of florid plasma cell infiltration have been reported in association with late antibody‐mediated rejection (ABMR) . Similar to our case, the infiltrated plasma cells in this variant of ABMR are mature and polyclonal, as verified by expression of both kappa and lambda light chains by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 80%